Kepemimpinan dan Jejak Tanya Terminologis: Uji Coba Dekonstruktif atas Pesan Al-Qur'an - Tufail, Ilfan; Hidayat, Aldi (Published by the Postgraduate Program in Islamic Education Management, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, Indonesia, 2022)
In its development, a talk on leadership is never dated to be studied. This leadership study will continue to be a topic of constant warmth, given its position in every system of human life. The leaders' positions and portions are widely analyzed from diverse perspectives. It all depends on which side one is on and assessing the issue of a leader in one's musical object. When leadership is reviewed from a political perspective, it begets a different understanding when studied from an educational, even economic perspective. The article tried to do a leadership review from an Islamic perspective, elaborating on passages from the Qur 'and thematically. Given the Islamic position with the motto of rahmatan Lil 'Alamin. Therefore, the teachings of Islam and the content of the Qur 'an must be a real foothold and a very important and strategic part to emerge. In this text, the approach used in analyzing the definitive substance and philosophical meaning of leadership is using the Derrida thought analysis, which are demonstrative.